Lysosomal-associated protein transmembrane 4 Beta-35 overexpression is a novel independent prognostic marker for gastric carcinoma. - Luying Liu; Xuefang Xu; Lili Jing; Gengyin Zhou; Zhang Cao; Yanchun Han; Rouli Zhou (PLoS ONE, 2015)
The purpose of this work was to analyze the relationships between the expression status of Lysosomal-associated protein transmembrane-4 beta 35 (LAPTM4B-35) in cancerous tissues and clinicopathological characteristics and prognosis of the patients with gastric carcinoma (GC).The GC samples from 157 patients in a discovery cohort and 148 patients in a testing cohort with follow-up data were used to validate the feasibility of expression of LAPTM4B-35 protein in predicting GC prognosis. Immunohistochemical staining was used to determine the expression of LAPTM4B-35 protein in precancerous gastric lesions and gastric carcinomas. The correlation between the expression of LAPTM4B-35 and clinicopathologic characteristics of patients with gastric carcinoma was analyzed using chi-square test. Univariate and multivariate analyses were performed to determine the association between LAPTM4B-35 expression and prognosis.LAPTM4B-35 expression was increased steadily in sequential stages of precancerous gastric lesions. Positive LAPTM4B-35 expression was more frequently detected in patients with distant metastasis (P = 0.023) and III+IV TNM stages (P = 0.042) in the discovery cohort. Kaplan-Meier survival curves and univariate analysis showed that expression of LAPTM4B-35 had a significant impact on overall survival of patients with gastric carcinoma in discovery cohort (P<0.001) and testing cohort (P = 0.001). LAPTM4B-35 expression was an independent prognostic indicator for the overall survival of patients with gastric carcinoma in both cohorts.The present research demonstrated that LAPTM4B-35 over-expression was an independent factor in gastric carcinoma prognosis. LAPTM4B gene may be a useful target of interventions slowing the progression of precancerous gastric lesions and a new therapy method to improve the prognosis of gastric carcinoma.